(untitled) (LIS TODAY, 2022)
The current study attempts to build an analysis of frame of mind of the students concerning the library management in the University of Jammu post COVID-19. Management is an activity of planning and perpetuating suitable conditions to obtain the desired performance and effectiveness in achieving objectives of the organisation. Management is multifaceted and its stretch is huge as it encompasses resources such as infrastructure, technology-based resources, manpower and economic resources.